I am David - Holm, Anne, 1922-; Kingsland, L. W. (London : Egmont., 2004)
After escaping from an Eastern European concentration camp where he has spent most of his life, a twelve-year-old boy struggles to cope with an entirely strange world as he flees northward to freedom in Denmark.
Q
Previously published under title: North to freedom.
b
b
Keywords: Refugees -- Fiction